Examining the quality of record linkage process using nationwide Brazilian administrative databases to build a large birth cohort - Almeida, Daniela (2020)
Health Surveillance Secretary, Ministry of Health, Brazil; Fundação de Amparo à Pesquisa do Estado da Bahia (FAPESB); Wellcome Trust (Grant number 202912 / Z / 16 / Z); Financiadora de Estudos e Projetos-FINEP; Secretary of Science and Technology of the State of Bahia-SECTI. ESP is funded by the Wellcome Trust (grant number 213589/Z/18/Z) However the funder of this study had no role in study design, data collection, data analysis, data interpretation, or writing of the report.